Evaluation of the anti-infective potential of the seed endophytic fungi of Corchorus olitorius through metabolomics and molecular docking approach - Arwa Mortada Ahmed; Ayman M. Ibrahim; Ramadan Yahia; Nourhan Hisham Shady; Basma Khalaf Mahmoud; Usama Ramadan Abdelmohsen; Mostafa A. Fouad (BMC Microbiology, 2023)
Abstract Background Endophytic fungi are very rich sources of natural antibacterial and antifungal compounds. The main aim of this study is to isolate the fungal endophytes from the medicinal plant Corchorus olitorius seeds (F. Malvaceae), followed by antimicrobial screening against various bacterial and fungal strains. Results Seven endophytic fungal strains belonging to different three genera were isolated, including Penicillium, Fusarium, and Aspergillus. The seven isolated endophytic strains revealed selective noticeable activity against Escherichia coli (ATCC25922) with varied IC50s ranging from 1.19 to 10 µg /mL, in which Aspergillus sp. (Ar 6) exhibited the strongest potency against E. coli (ATCC 25,922) and candida albicans (ATCC 10,231) with IC50s 1.19 and 15 µg /mL, respectively. Therefore, the chemical profiling of Aspergillus sp. (Ar 6) crude extract was performed using LC-HR-ESI-MS and led to the dereplication of sixteen compounds of various classes (1–16). In-silico analysis of the dereplicated metabolites led to highlighting the compounds responsible for the antimicrobial activity of Aspergillus sp. extract. Moreover, molecular docking showed the potential targets of the metabolites; Astellatol (5), Aspergillipeptide A (10), and Emericellamide C (14) against E. coli and C. albicans. Conclusion These results will expand the knowledge of endophytes and provide us with new approaches to face the global antibiotic resistance problem and the future production of undiscovered compounds different from the antibiotics classes.